The damaging November 2022 Mw 5.6 earthquake in West Java, Indonesia - Yun, S. (2023)
On 21 November 2022, a MW 5.6. earthquake hit Cianjur area in West Java, Indonesia. The small magnitude earthquake claimed 329 people’s lives, and about 114,414 people were taking shelter in refugee camps as of 1 December 2022 according to the National Disaster Mitigation Agency (BNPB) of Indonesia. We produced maps of coseismic deformation and surface disturbance (a.k.a. Damage Proxy Map, DPM) using Synthetic Aperture Radar (InSAR) data acquired by the ALOS-2 satellite about 11 hours after the earthquake. We combine and analyze ground observations, coseismic deformation and surface disturbance maps derived from ALOS-2 and Sentinel-1 SAR data, seismic waveforms of the mainshock and aftershocks, high-rate GNSS data, and tiltmeter data to characterize the source parameters of the earthquake and damage caused by the strong ground motion, landslides, and liquefaction, and study the potential impact of the event on the geohazards of the area.